2005
DOI: 10.1007/s00418-005-0051-7
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin in the assessment of aberrant placental cytotrophoblast turnover in pregnancies complicated by pre-eclampsia

Abstract: E-cadherin is a cell-cell adhesion protein expressed in cytotrophoblasts, which is lost as they differentiate and syncytialise. We have exploited E-cadherin as a marker of cytotrophoblasts to investigate villous tissue composition in first and third trimester placentae, both in normal pregnancy and pregnancies complicated by pre-eclampsia. We have achieved this by measuring expression levels of E-cadherin at the mRNA level, using Q-PCR, and at the protein level using semi-quantitative Western blotting. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 32 publications
(30 reference statements)
5
49
0
1
Order By: Relevance
“…Dual labeling of Mtd with cyclin E1 revealed that Mtd was present during the G 1 phase of the cell cycle in the early first trimester CTs of floating and anchoring villi (Figure 2a, data not shown), with coexpression decreasing in the late first trimester (data not shown). To confirm that Mtd expression was localized to CTs during the early first trimester, we performed coexpression studies of Mtd with the cytotrophoblast marker, E-cadherin 33 ( Figure 2b). It is noted that Mtd expression was not restricted to cyclin E1-positive cells, as cells that were presumably undergoing mitosis, as shown by chromosomal patterning (Figure 2c) and Ki67 (Figure 2c, bottom panel), also displayed Mtd expression in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Dual labeling of Mtd with cyclin E1 revealed that Mtd was present during the G 1 phase of the cell cycle in the early first trimester CTs of floating and anchoring villi (Figure 2a, data not shown), with coexpression decreasing in the late first trimester (data not shown). To confirm that Mtd expression was localized to CTs during the early first trimester, we performed coexpression studies of Mtd with the cytotrophoblast marker, E-cadherin 33 ( Figure 2b). It is noted that Mtd expression was not restricted to cyclin E1-positive cells, as cells that were presumably undergoing mitosis, as shown by chromosomal patterning (Figure 2c) and Ki67 (Figure 2c, bottom panel), also displayed Mtd expression in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…14 Furthermore, immunohistochemical and morphometric analyses of preeclamptic placentae revealed an increase in proliferative activity of cytotrophoblast. 31,32 Therefore, these diseases might represent divergent end points resulting from Understanding the mechanisms that govern CT cell survival in the human placenta, and the selective expression of GCM1 in CT destined for syncytial fusion or in EV-CT remodeling spiral arteries will improve our perception of the early origins of severe IUGR and preeclampsia caused by the so-called 'placental insufficiency.' Further studies of GCM1 regulation, together with an integration of stereologically determined villous trophoblast structure, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…90 Increased E-cadherin expression in PE may reflect excessive trophoblast proliferation, or impaired trophoblast differentiation, either of which could have adverse consequences. 91 E-cadherin protein levels are also significantly higher in PE placentae compared with normotensive placentae. 51 Thus, it was also suggested that cadherin modulation is defective in PE, as it was shown that VE-cadherin was not adequately upregulated in trophoblasts for interaction with maternal vessels.…”
Section: Altered Expression Of Emt Inducers Transcription Factors Anmentioning
confidence: 91%